JUDICIAL NARRATIVE SOVEREIGNTY: NORMALIZATION OF EMERGENCY THROUGH UNCONSTITUTIONAL CONSTITUTIONAL AMENDMENTS IN TIMES OF CRISIS - Belov, Martin (Pravni zapisi, 2026)
This paper explores the role of the courts in times of crisis and emergency. It focuses on the tension between the imaginary conceptualizations regarding the status of courts in times of normalcy and emergency that exist in the theoretical discourse and the constitutional anthropology and the empirical ways the courts contribute to the normalization of emergency in socio-legal practice by justifying crisis and emergency as “the new normal”. The paper outlines several key constitutional imaginaries related to the courts in times of normalcy. The imaginaries are structured through analytical reconstruction of the main approaches to the concept of courts provided in modern consti- tutionalism in pursuit of justifying the proper engagement of courts in the constitutional crisis management. This reconstruction is meant to produce both novel approaches to the role of the courts and an original typology of the imaginaries of the courts.
Keywords: narrative; sovereignty; emergency crisis; constitutional amendment; courts; constitutional courts; constitutional imaginaries